The Effects of Enlarged Adenoids on a Developing Malocclusion - Kevin Wıllıams; Derek Mahony (Galenos Yayinevi, 2008)
This article reviews upper airway obstruction caused by hypertrophied adenoids and the possibilities of a subsequent malocclusion. Early diagnosis and treatment of pathological conditions that can lead to the obstruction of the upper airways is essential to anticipate and prevent alterations in dental arches, facial bones and muscle function. Correct nasal breathing facilitates normal growth and development of the craniofacial complex. Important motor functions such as chewing and swallowing depend largely on normal craniofacial development. Any restriction to the upper airway passages can cause nasal obstruction possibly resulting in various dentofacial and skeletal alterations. Upper respiratory obstruction often leads to mouth breathing. Habitual mouth breathing may result in muscular and postural anomalies which may in turn cause dentoskeletal malocclusions. Hypertrophy of the adenoids, and palatine tonsils, are one of the most frequent causes of upper respiratory obstruction. Philosophies regarding the treatment of adenoid hypertrophy range from dietary control and environmental modifications to dentofacial orthopedics change of breathing exercises, and surgical procedures.